Expression of VEGFA‐regulating miRNAs and mortality in wet AMD. Issue 12 (21st October 2019) - Blasiak, Janusz; Watala, Cezary; Tuuminen, Raimo; Kivinen, Niko; Koskela, Ali; Uusitalo‐Järvinen, Hannele; Tuulonen, Anja; Winiarczyk, Mateusz; Mackiewicz, Jerzy; Zmorzyński, Szymon; Filip, Agata; Kaarniranta, Kai
Abstract: MicroRNAs (miRNAs) regulate gene expression; many of them act in the retinal pigment epithelium (RPE), and RPE degeneration is known to be a critical factor in age‐related macular degeneration (AMD). Repeated injections with anti‐VEGFA (vascular endothelial growth factor A) are the only effective therapy in wet AMD. We investigated the correlation between the expression of 18 miRNAs involved in the regulation of the VEGFA gene in serum of 76 wet AMD patients and 70 controls. Efficacy of anti‐VEGFA treatment was evaluated by counting the number of injections delivered up to 12 years. In addition, we compared the relative numbers of deaths in patient with AMD and control groups. We observed a decreased expression of miR‐34‐5p, miR‐126‐3p, miR‐145‐5p and miR‐205‐5p in wet AMD patients as compared with controls. These miRNAs are involved in the regulation of angiogenesis, cytoprotection and protein clearance. No miRNA was significantly correlated with the treatment outcome. Wet AMD patients had greater mortality than controls, and their survival was inversely associated with the number of anti‐VEGFA injections per year. No association was observed between miRNA expression and mortality. Our study emphasizes the need to clarify the role of miRNA regulation in AMD pathogenesis.